CORPORATE GOVERNANCE AND SUSTAINABILITY PRACTICES OF ENERGY COMPANIES IN INDIA - Chhabra, Ankur; Sharma, Sanjay Kumar; Chhabra, Monica (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In order to better understand how energy firms in India approach problems of corporate responsibility, sustainability, and regulatory compliance, the goal of this research is to analyze the various approaches that these companies use. It focuses on the processes that they use in a variety of different areas of practice. As a result of the fact that India has one of the energy markets that is increasing at the fastest rate around the globe, energy firms have a significant impact on the path that India is on towards achieving sustainable development. Within the scope of this study, the key objectives are to explore the reporting procedures, governance structures, and sustainability activities of major energy businesses in India.